GE_GERICHTE C/17297/2016 vom 25. Juli 2018 - GE Cour de justice (2018)
DIVORCE ; ACTION EN MODIFICATION ; DROIT DE GARDE ; GARDE ALTERNÉE ; OBLIGATION D'ENTRETIEN ; ENFANT | CC.134; CC.286.al2; CC.298.al2.letter